Wands and charms - Lindsay, Elizabeth; Currey, Anna (Usborne London, 2009)
It's Lilac Blossom's first day at Fairy Charm School and already Princess Bee Balm is bossing the other fairies around. Join Lila as she finds her feet at Silver Spires - meeting teachers, making friends, and breaking rules. Will Lila be expelled from Fairy Charm School before she's even cast her first spell in class?